Creation and Preclinical Testing of a Spirometer with Extended Functionality - V. S. Shabaev; V. A. Onoshko; A. S. Galushko; V. A. Mazurok; I. V. Orazmagomedova; L. G. Vasilyeva; D. A. Aleksandrova (Неотложная медицинская помощь, 2024)
RELEVANCE. We present the results of preclinical testing of an upgraded portable AR1 gas flow analyzer produced by JSC Krasnogvardeets (Saint Petersburg) in order to create import-substituting technologies and develop practical and scientific spheres of healthcare.THE AIM OF THE STUDY. was to substantiate the possibility of clinical use of the upgraded device, originally intended for testing ventilators and inhalation anesthesia devices, as a monitor of the external respiration apparatus function.MATERIAL AND METHODS. The preclinical study of the upgraded gas flow analyzer was conducted at the V.A. Almazov National Medical Research Center in comparison with devices for conventional (Bellavista 950, Berner Ross Medical, Russia) and high-frequency (IPV-2C, Intrapulmonary Percussive Ventilation, Percussionaire Corporation, USA) mechanical ventilation in volume- and pressure-controlled modes using an artificial lung. The following reflected spirometry parameters were compared: tidal and minute volume under inhalation and exhalation, respiratory rate, maximum and minimum flows, peak and positive end expiratory pressure, fraction of inspired oxygen.RESULTS. A high accuracy of parameter matching shown by the gas flow analyzer and ventilators was demonstrated.CONCLUSION. The upgraded model of the gas flow analyzer can be used clinically as a portable spirometer at the prehospital and hospital stages.